δ13C and δ15N Variability in Modern Guanaco (Lama guanicoe) Assemblages in Southern Patagonia: Implications for Zooarchaeological Studies - Tessone, Augusto (2014)
We study the isotopic variability of modern social groups of guanacos (Lama guanicoe) and discuss the implications of these results for the analysis of archaeofaunas from archaeological sites of Patagonia. The aim of this work is to evaluate whether the study of the isotope composition of carbon and nitrogen from collagen (δ 13C and δ 15N) is a methodology that allows the discussion of hunting strategies – individual versus mass – carried out by human populations in this particular case of the guanaco from southern Patagonia. Samples come from five modern assemblages of guanacos located in the west margin of the Cardiel Lake and are the result of a catastrophic mortality episode produced by winter stress. The isotopic variability of these samples is compared with that of a mesoregional attritional assemblage built from multiple sites and chronologies. The results indicate, in the first place, that there is no differentiation between males and females, second, that the offspring show no increase of signals when compared to the other age categories and finally, juveniles recorded the lowest δ 15N values. In relation to the main purpose of this research, measurements of variability from modern assemblages and the attritional groups have been compared. The three assemblages with lower variability are modern ones. However, the two remaining modern assemblages record a variability higher than or equal to the attritional groups. Thus, for southern Patagonian guanacos, the hypothesis that proposes that the isotopic variability of a herd would be lower than the one obtained from multiple populations and different hunting events is rejected. Finally, we analyze the possible causes for these results together with situations in which δ 13C and δ 15N can be used in the study of the guanaco hunting strategies in southern Patagonia.